1999
DOI: 10.1016/s0893-6080(99)00052-0
|View full text |Cite
|
Sign up to set email alerts
|

Unsupervised visual learning of three-dimensional objects using a modular network architecture

Abstract: This paper presents a modular network architecture that learns to cluster multiple views of multiple three-dimensional (3D) objects. The proposed network model is based on a mixture of non-linear autoencoders, which compete to encode multiple views of each 3D object. The main advantage of using a mixture of autoencoders is that it can capture multiple non-linear sub-spaces, rather than multiple centers for describing complex shapes of the view distributions. The unsupervised training algorithm is formulated wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2001
2001
2011
2011

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…[9] showed that mixtures of autoencoders are able to specialize in different handwritten digit classes. [12] used the reconstruction error of modular autoencoders in the weight updates to force the output of at least one module to fit the input, and to force the rest of the modules to increase the error between the input and the output. [13] used a neural gas mixture of local principal component analyses.…”
Section: Related Workmentioning
confidence: 99%
“…[9] showed that mixtures of autoencoders are able to specialize in different handwritten digit classes. [12] used the reconstruction error of modular autoencoders in the weight updates to force the output of at least one module to fit the input, and to force the rest of the modules to increase the error between the input and the output. [13] used a neural gas mixture of local principal component analyses.…”
Section: Related Workmentioning
confidence: 99%
“…This learning process is based on on-line processing without a teacher, and is also additive learning in which new objects are provided from time to time. Attempting the partial realization of these functions on a computer, one of the authors adopted a competitive modular learning scheme [1,2], and proposed a model by which some three-dimensional objects are recognized and classified without a teacher based on their two-dimensional images projected from various viewpoints [3,4]. This method realized unsupervised clustering in which continuously distributed data are regarded as a class.…”
Section: Introductionmentioning
confidence: 99%
“…In this work we attempt to achieve the above goal by enhancing the learning procedure of the past 3D object recognition model [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been many studies on technology of recognizing a 3D object from its 2D image. As example, parametric eigenspace method [7]; neural networks [8,9]; self-organizing neural architecture called VIEWNET [2]; and modular neural networks [10]. Section 2 describes a proposed 3D model to recognize 3D objects based on the Hu and Zernike moment invariants.…”
Section: Introductionmentioning
confidence: 99%